Pembrolizumab for advanced prostate adenocarcinoma: findings of the KEYNOTE-028 study. (9th July 2018) - Hansen, A R; Massard, C; Ott, P A; Haas, N B; Lopez, J S; Ejadi, S; Wallmark, J M; Keam, B; Delord, J -P; Aggarwal, R; Gould, M; Yang, P; et al.
Abstract: Background: Patients with castration-resistant prostate cancer derive only modest clinical benefit from available therapies. Blockade of the inhibitory programmed death 1 (PD-1) receptor by monoclonal antibodies has been effective in several malignancies. Results from the prostate adenocarcinoma cohort of the nonrandomized phase Ib KEYNOTE-028 trial of pembrolizumab in advanced solid tumors are presented. Materials and methods: Key eligibility criteria included advanced prostate adenocarcinoma, unsuccessful standard therapy, measurable disease per Response Evaluation Criteria in Solid Tumors, version 1.1 (RECIST v1.1), and PD-1 ligand (PD-L1) expression in ≥1% of tumor or stromal cells. Patients received pembrolizumab 10 mg/kg every 2 weeks until disease progression or intolerable toxicity for up to 24 months. Primary end point was objective response rate (ORR) per RECIST v1.1 by investigator review. Results: Median patient age in this cohort ( n = 23) was 65 years; 73.9% of patients received at least two prior therapies for metastatic disease. There were four confirmed partial responses, for an ORR of 17.4% [95% confidence interval (CI) 5.0%–38.8%]; 8 of 23 (34.8%) patients had stable disease. Median duration of response was 13.5 months. Median progression-free survival (PFS) and overall survival (OS) were 3.5 and 7.9 months, respectively; 6-month PFS and OS rates were 34.8% and 73.4%, respectively. One patient remained on treatment at data cutoff. After a median follow-up of 7.9 months, 14 (60.9%) patients experienced treatment-related adverse events (TRAEs), most commonly nausea ( n = 3, 13.0%). Four (17.3%) experienced grade 3/4 TRAEs: grade 3 peripheral neuropathy, grade 3 asthenia, grade 3 fatigue, and grade 4 lipase increase. No pembrolizumab-related deaths or discontinuations occurred. Conclusion: Pembrolizumab resulted in durable objective response in a subset of patients with heavily pretreated, advanced PD-L1–positive prostate cancer, and its side effect profile was favorable. ClinicalTrials.gov Identifier: NCT02054806